(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2024)
The use of alternative matrices in toxicological analyses has increased in forensic toxicological analysis. Alternative samples to blood, visceral organs, and urine are useful for reliability and comprehensiveness regarding generating toxicological profiles. The article critically reviews recent literature on alternative matrices like oral fluid, hair, skeletal tissue, sweat, cerebrospinal fluid, meconium, breast milk, and vitreous humor and their applications in forensic toxicology. It analyzes the characteristics, advantages, limitations, and applications of alternative matrices in drug and poison analysis. This review article further discusses the characteristics of biological matrices used in forensic analyses as substitutes for whole blood, urine, and viscera samples. Each matrix type has advantages regarding sampling, preservation, extraction methods, detection time frame, drug levels, and other factors. However, these matrices also have limitations, such as limited drug incorporation, correlation with concentrations for effects, low xenobiotic levels, and the need for proper sample preparation and analysis. Although there is data on detecting traditional drugs of abuse in alternative matrices, information on the detection of emerging illicit drugs in these matrices is scarcer. Alternative biological specimens play a crucial role in forensic toxicology, but they come with distinct limitations and characteristics that must be considered. The results from analyzing these samples may differ based on the type of specimen. Alternative matrices will remain a focus in forensic toxicology due to their benefits and potential use when blood, urine, or visceral organs are inaccessible or impractical, particularly in cases like drug-facilitated sexual assault, burnt bodies, or decomposed remains.